Psychological analysis of women migrant workers in women empowerment issue - Erhamwilda, Erhamwilda (2016)
One of the most important issues concerning women empowerment is women prosperity improvement through the improvement of women’s roles in work places.Becoming migrant workers is one of the choices that women have for improving their economic role. Facts show that the improvement of women’s economic role does not automatically improve their value. From the perspective of MDG’s targets of achievement, women empowerment by means of becoming migrant workers may eliminate poverty, its psychological impacts, however, require an analysis.The main question that this research is trying to answer is “What may constitute psychological impacts that women and their families may have, from the perspectives of Gender Mainstreaming, if they become migrant workers.In particular, this paper is trying to answer the following questions: (1) what sorts of problems and sources of problems that women migrant workers have?; (2) how to implement women empowerment among women migrant workers from the perspective of “gender mainstreaming”?; (3) how to fulfill psychological needs of women migrant workers?. This research is a qualitative analysis of cases concerning women migrant workers employing an expos de facto method.The implication of this research is the needs for an international convention among senders and receivers of women migrant workers in order to respond the implementation of women migrant workers empowerment.